Understanding Faculty Development As Capacity Development: A Case Study From South Africa - Frantz, J; Rhoda, A; Murdoch-Eaton, Deborah; Sandars, John; Marshall, Michelle; Burch, Vanessa Celeste (My University, 2022)
Background Faculty-development programmes for health professions educators focus on capacity building, which may not recognise the pre-existing skills and knowledge of participants. A shift to capacity development that recognises the individual and collective skills and knowledge of faculty is needed. Objectives To explore the contribution an African faculty-development programme made to the professional and personal development of faculty and teaching in the programme. Also, to investigate the contribution the programme made to the wider health professions education community of practice in Africa. Methods A qualitative, exploratory design was used, with a convenience sample of 15 faculty members of the sub-Saharan Africa-Foundation for Advancement of International Medical Education and Research (FAIMER) Regional Institute (SAFRI) faculty development programme. Each participant’s SAFRI journey was explored through an in-depth interview, and data were thematically analysed. Ethical approval was obtained for the study. Results A model of faculty development for individual and collective capacity development was derived from five emergent themes: (i) personal and professional development; (ii) collaborative practice; (iii) networking; (iv) research and scholarship; and (v) support. Conclusions Faculty-development initiatives may result in capacity development, which extends beyond individual participants to include a wider community of practice. This expanded understanding is best articulated by the African term ubuntu (I am because you are).
Keywords: Medical and Health Sciences not elsewhere class; Capacity development; Faculty development